Communication Strategy in Crisis Management of PT Persib Bandung Bermartabat (PBB) (Case Study of PT PBB's Communication Strategy in Managing the Crisis After the Termination of the 2020-2021 Liga 1) - Septian Nugraha; Neni Yulianita; Dadan Mulyana (Dinasti International Journal of Education Management And Social Science, 2025)
The name Persib Bandung on the Indonesian football scene is respected because of its status as a legendary and outstanding team in Indonesian football. Persib's achievements in Indonesian football are not only limited to the big names and achievements they have achieved. More than that, Persib also managed to maintain its existence as a great team for 88 years. Especially in the current era of the football industry. Since the Indonesian football competition entered the industrial realm, Persib has been listed as the team with the best finances. In 2017, Forbes magazine named Persib as the richest team in Indonesia. Apart from that, when the crisis of stopping competition hit, Persib was one of the teams that was able to recover quickly. This is what attracted researchers' interest in making Persib a research subject, especially in terms of crisis management carried out by PT Persib Bandung Bermartabat (PBB) as the company that oversees the management of the Persib team in maintaining Persib's existence as a big team in Indonesia. Because, along the way, especially in the era of the Indonesian football industry, there have been a number of incidents that could potentially cause a crisis for Persib. As happened in 2020 when the competition was stopped due to the Covid-19 pandemic. The research uses qualitative methods with a case study approach. The data collection technique is through in-depth interviews, observation and document search. This research produces a model of the stages of crisis management and communication carried out by PT Persib Bandung Bermartabat (PBb) in dealing with the crisis of ending the 2020-2021 Liga 1. In the research, it was also discovered how PT PBB's reforms were carried out in maintaining the existence of Persib Bandung in the Indonesian football arena.